Effects of prescribed fire timing on vigor of sericea lespedeza in the Kansas Flint Hills - Alexander, Jonathan Andrew (Kansas State University, 2018)
We evaluated effects of annual, prescribed burning on vigor of the noxious weed, sericea lespedeza (Lespedeza cuneata; SL) in native tallgrass prairie over a 4-yr period. We hypothesized that annual prescribed burning conducted during the growing season would selectively pressure SL, whereas locally-conventional, dormant-season prescribed burning would have no effect on SL. A 50-ha native tallgrass pasture infested with SL (initial basal frequency = 2 ± 1.3%, initial aerial frequency = 36 ± 3.4%) was used for our study. It was divided along watershed boundaries into 9 fire-management units (5 ± 2.6 ha) for this experiment. Burn units were assigned randomly to 1 of 3 prescribed-burning times (n = 3 / treatment): early spring (1 April; EARLY), mid-summer (1 August; MID), or late summer (1 September; LATE). Forage biomass, SL aerial frequency, SL stem length, SL seed production, soil cover, and plant species composition were measured along single, permanent 100-m transects in each burn unit. Treatment and measurement date influenced forage biomass and SL stem length (treatment × time). Forage biomass was not different (P ≥ 0.43) between treatments on 17 July; however, forage biomass was greater (P < 0.01) in EARLY than MID and greater in MID than LATE on 10 October. Maximum stem length of SL was less (P ≤ 0.02) in MID and LATE than in EARLY on 17 July and on 10 October. Aerial frequency of SL was least (main effect – P < 0.01) in LATE, intermediate in MID, and greatest in EARLY, whereas basal frequency of SL was less (P < 0.01) in MID and LATE compared with EARLY. Whole-plant dry weight and seed production of SL at dormancy were greatly diminished (P ≤ 0.02) in MID and LATE compared with EARLY. Occurrence of bare soil, litter cover, and total basal plant cover were not different (P ≥ 0.21) between treatments. Similarly, basal cover of grasses, forbs, and shrubs were not different (P ≥ 0.24) between treatments. We interpreted these data to indicate that annual prescribed burning during the growing season had strong suppressive effects on SL compared to locally-conventional, early-season prescribed burning and produced no apparent detrimental effects on soil cover or non-target plant species. Post-fire regrowth was sufficient to prevent erosion and soil-moisture loss during the subsequent dormant season and would have allowed light to moderate grazing during the ensuing winter. Key words: Lespedeza cuneata, prescribed fire, range improvement
Keywords: Sericea Lespedeza; Lespedeza cuneata; Prescribed burning; Tallgrass prairie; Range restoration; Invasive species